Cubitus valgus and tardy ulnar nerve palsy due to an intracapsular ulnar nerve - Sharma, Manish S. (Springer US, 2013)
BACKGROUND: We describe a patient with tardy ulnar neuropathy and cubitus valgus deformity found to have an intracapsular ulnar nerve. METHODS: An 89-year-old woman presented with severe neuropathic pain in the ulnar digits of the hand, advanced degenerative arthritis of the elbow, and tardy ulnar nerve palsy. Her pain was exacerbated with elbow movement, particularly flexion. She had paralysis of ulnar nerve innervated muscles, hypersensitivity with absence of two-point discrimination in her ulnar 1–1/2 digits, and a fixed ulnar claw deformity. She also had a grossly unstable elbow. RESULTS: Plain films revealed a cubitus valgus deformity (38°), an absent radial head, a dislocated proximal radioulnar joint and advanced arthritic changes. Ultrasonography revealed an indistinct ulnar nerve within the cubital tunnel which penetrated the joint. Electrophysiological studies revealed evidence of a severe ulnar neuropathy at the level of the elbow. Intraoperatively, an attenuated 2 cm length of the retrocondylar ulnar nerve was observed to be incorporated into the joint capsule tethered by a fibrous/synovial band which was released. A large effusion was drained. The ulnar nerve was transposed subcutaneously. The capsular rent was repaired in layers. She noted immediate and sustained (2 year follow-up) pain relief and regained moderate function in her interossei. CONCLUSIONS: We believe that the chronic cubitus valgus deformity and secondary degenerative elbow joint changes led to an altered course of the nerve and attenuation of the medial joint capsule such that the ulnar nerve spontaneously buttonholed itself intra-articularly.